Asset Dissemination Through Dealer Markets - Colliard, Jean-Edouard; Demange, Gabrielle (Management Science, 2021)
In over-the-counter markets for assets, such as bonds and securitizations, large volumes can be split into smaller pieces and gradually sold to several final investors with the intermediation of multiple dealers. This paper proposes a model to study this process, called asset dissemination. A dealer buys several units of an asset from a customer and then sells some units to the dealer’s customers and to a second dealer, who sells to the second dealer’s customers and to a third dealer, and so on. The extent of dissemination is measured by the number of dealers involved and the total customer demand served. We show that asymmetric information on customer demand hinders both dimensions of dissemination. We also study how the quantity to disseminate and the dealers’ funding costs impact dissemination and the prices and quantities in interdealer transactions. This paper was accepted by Gustavo Manso, finance.